"Biomethanation of syngas by enriched mixed anaerobic consortium in pressurized agitated column". (October 2021) - Figueras, J.; Benbelkacem, H.; Dumas, C.; Buffiere, P.
Highlights: A continuous pressurized bioreactor has been run for syngas biomethanation. A high methane productivity and high CO and H2 conversions were achieved. CO inhibition on carboxydotrophs was a possible cause of limitation. Abstract: In a circular economy approach, heterogeneous wastes can be upgraded to energy in the form of syngas via pyrogasification, and then to methane via biomethanation. Working at high pressure is a promising approach to intensify the process and to reduce gas–liquid transfer limitations. However, raising the pressure could lead to reaching the CO inhibition threshold of the microorganisms involved in syngas-biomethanation. To investigate the impact on pressure on the process, a 10 L continuous stirred tank reactor working at 4 bars and 55 °C was implemented. Syngas (40% CO, 40% H2, 20% CO2 ) biomethanation was performed successfully and methane productivity as high as 6.8 mmolCH4 /Lreactor /h with almost full conversion of CO (97%) and H2 (98%) was achieved. CO inhibition was investigated and carboxydotrophs appeared less resistant to high CO exposition than methanogens.